2016
DOI: 10.1007/s10508-016-0819-y
|View full text |Cite
|
Sign up to set email alerts
|

The Geography of Sexual Orientation: Structural Stigma and Sexual Attraction, Behavior, and Identity Among Men Who Have Sex with Men Across 38 European Countries

Abstract: While the sexual identity and behavior of men who have sex with men (MSM) varies across countries, no study has examined country-level structural stigma toward sexual minorities as a correlate of this variation. Drawing on emerging support for the context-dependent nature of MSM’s open sexual self-identification cross-nationally, we examined country-level structural stigma as a key correlate of the geographic variation in MSM’s sexual attraction, behavior, and identity, and concordance across these factors. Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 52 publications
3
45
0
Order By: Relevance
“…Future research can build on these findings by testing the causal sequence from stress exposure to these co-occurring outcomes and the potential causal influence of these outcomes on each other. Further, given that the social climate surrounding sexual minorities varies widely across world countries [ 59 – 61 ], future studies should also explore the extent to which the current findings generalize across countries. Such studies, for instance, might take advantage of the wide variation in social climates surrounding sexual minorities to predict sexual orientation disparities in psychosocial health outcomes and mediators from this variation.…”
Section: Discussionmentioning
confidence: 99%
“…Future research can build on these findings by testing the causal sequence from stress exposure to these co-occurring outcomes and the potential causal influence of these outcomes on each other. Further, given that the social climate surrounding sexual minorities varies widely across world countries [ 59 – 61 ], future studies should also explore the extent to which the current findings generalize across countries. Such studies, for instance, might take advantage of the wide variation in social climates surrounding sexual minorities to predict sexual orientation disparities in psychosocial health outcomes and mediators from this variation.…”
Section: Discussionmentioning
confidence: 99%
“…Non-disclosure of sexual orientation amongst MSMW has been attributed to high levels of perceived stigma, as well as certain legal, cultural, and social norms (22). Such barriers to disclosure have been argued to drive MSMW underground and place them out of reach of HIV-preventative services, knowledges, and behaviours, thereby increasing their risk for HIV infection (23) (24).…”
Section: Introductionmentioning
confidence: 99%
“…Although the change in social norms can be difficult to estimate the most relevant changes include the change in Massachusetts State law allowing for same sex marriage in 2013 and the repeal by the Federal Supreme Court of portions of the Defense of Marriage Act in 2015. There is emerging evidence that the changing political climate can exert a positive influence on sexual minority mental health (e.g., Hatzenbuelher et al, 2010; Pachankis et al, 2017) and may impact the present day relevance of the current findings. In addition the passing of the Affordable Care Act, and subsequent legislation has changed access to health insurance and health care for many Americans, which may limit the current applicability of our findings.…”
Section: Discussionmentioning
confidence: 75%
“…In particular, recent research on structural stigma and sexual orientation-related health disparities has demonstrated that improving social climates—including social policies that differentially target gays and lesbians (e.g., same-sex marriage and adoption)—may reduce mental health problems within sexual minority populations (Hatzenbuelher et al, 2010; Oldenburg et al, 2015; Pachankis et al, 2017). Thus, developing and evaluating structural interventions that reduce sexual minority stigma and discrimination, the major drivers of syndemic processes, represent an important avenue for future research.…”
Section: Discussionmentioning
confidence: 99%